Molecular Characterization of Infectious Bursal Disease Virus Isolated from Broiler Chickens in Bangladesh - Islam, M.A.; Rahman, M.M.; Islam, M.R.; Khatun, M.M. (International Journal of Poultry Science, 2004)
An attempt was undertaken for molecular characterization of infectious bursal disease virus (IBDV) field isolates. In order to isolate the virus, bursae of thirty five dead chicken with clinical infectious bursal disease (IBD) were collected from Bangladesh Agricultural University (BAU), Mymensingh. Isolation of field strain of IBDV was carried out in chickens of 5-week-old. Five IBDV isolates were obtained from chicken inoculation. Reverse transcriptase-polymerase chain reaction (RT-PCR) was preformed to detect IBDV isolates in the bursal tissues. RT-PCR couple with restriction enzyme (RE) analysis was carried out for molecular characterization of IBDV isolates to determine the pathotype. 677 bp fragments from IBDV genome segment A corresponding to the hyper variable domain of outer capsid protein VP2 was amplified by RT-PCR. Two restriction endonuclease (REs), SspI and SacI were used for digestion of RT-PCR products. RT-PCR product was digested by SspI but not SacI. The presence of SspI restriction site in the 677 bp RT-PCR fragment indicated that IBDV isolates belonging to very virulent (vv) pathotype.